The Effect of Flexi-time on The Performance of X Hospital Administration Employees in Batu City, East Java, Indonesia: Mediating Role of Work-Life Balance, Job Satisfaction and Employee Loyalty - Mahendra, Deny; Kurniawati, Desi Tri (Journal of Business and Management Review, 2024)
Research Aims: The objectives of this research are to investigate the impact of flextime on the performance of administrative employees at Hospital X in Batu City, East Java, Indonesia, and to examine the mediating roles of work-life balance and job satisfaction. Specifically, the study aims to determine the direct and indirect effects of flextime on employee performance, analyze  the relationships between flextime, work-life balance, and job satisfaction, and identify the factors influencing the effectiveness of flextime arrangements. The research aims to provide insights into the implementation of flextime policies that enhance employee performance, work-life balance, and job satisfaction, ultimately contributing to improved organizational outcomes. Design/methodology/approach: The population in this study was all administrative personnel of Hospital X Batu City, East Java. Indonesia The sampling technique uses proportional random sampling with a sample of 112 respondents. Data were collected through questionnaires with Likert scales. The data is then analyzed using SEM-PLS with the help of SmartPLS application. Research Findings: The results of this study show that flexi-time has an effect on employee performance, while work-life balance and job satisfaction have an effect on mediating employee performance. Based on the results of flexi-time research is the result of the development of work-life balance that improves employee performance effectively and efficiently. Work-life balance and job satisfaction act as partial mediations on the effect of flexi-time on employee performance. Theoretical Contribution/Originality : The theoretical contribution of this research lies in its comprehensive examination of the impact of flextime on the performance of administrative employees at Hospital X in Batu City, East Java, Indonesia. The study explores the mediating role of work-life balance and job satisfaction in this relationship, providing valuable insights into the factors that influence employee performance in the hospital sector. This contribution is significant, as it addresses a pressing issue in the healthcare industry and offers practical recommendations for hospital administrators seeking to optimize employee performance and overall organizational Keywords: Flexi-time, work-life balance, job satisfaction, employee performance, hospital sector